Penerapan Media Pembelajaran Alat Peraga Matematika untuk Meningkatkan Kemampuan Pemahaman Matematis Peserta Didik - Meiannaristi, Isnaini; Sundi, Venni Herli; Hadi, Muhammad Sofian; Sugiyanti, Sugiyanti (Universitas Cokroaminoto Palopo, 2024)
The use of teaching aids in the learning process is a necessity in the world of education to improve students' mathematical understanding abilities. Students' abilities are the core of all knowledge transfer processes provided by teachers to students. Learning that is interesting and provides meaningful understanding can create a learning atmosphere and increase understanding abilities. The aim to be achieved in this research is to determine the increase in students' mathematical understanding abilities by applying mathematical teaching aids. The type of research used in this research is Classroom Action Research or PTK. The results of the research were that there was an increase in mathematical understanding ability as seen in the results of the post test carried out in each cycle with complete details in cycle 1 amounting to 67.8% and in cycle 2 amounting to 89.2%